Correlation between surface tension, work of adhesion in liquid metals/ceramic systems, and acoustic parameters - Hadef, Z.; Doghmane, A.; Kamli, K.; Hadjoub, Z. (Успехи физики металлов, 2018)
In the paper, a correlation between acoustic velocities V, elastic moduli M, and densities ρ, with surface tension σm, and work of adhesion Wad of different liquid metals on a given ceramic is studied and demonstrated. Simulation program is developed and used for scanning acoustic microscopy (SAM) under operating conditions, which favour the generation of acoustic waves. As found, for the given systems, all investigated acoustic parameters exhibit good dependences with both σm and Wad. Analysis and quantification of the results lead to the determination of semi-empirical formulas. В статті вперше демонструється кореляція між акустичними швидкостями V, пружніми модулями M, густинами ρ та поверхневим натягом σm, а також роботою адгезії Wad різних рідких металів на фіксованій кераміці. Використовується обчислювальна програма для сканувального акустичного мікроскопу (САМ) за умов, що є сприятливими задля ґенерування акустичних хвиль. Виявлено, що для конкретних систем усі досліджені акустичні параметри демонструють хорошу залежність від поверхневого натягу та роботи адгезії. Аналіза та кількісне визначення результатів привели до встановлення напівемпіричних формул. В статье исследуется и впервые демонстрируется корреляция между акустическими скоростями V, упругими модулями M, плотностями ρ и поверхностным натяжением σm, а также работой адгезии Wad различных жидких металлов на фиксированной керамике. Используется вычислительная программа для сканирующего акустического микроскопа (САМ) в условиях, благоприятных для генерирования акустических волн. Обнаружено, что для конкретных систем все исследованные акустические параметры демонстрируют хорошую зависимость от поверхностного натяжения и работы адгезии. Анализ и количественное определение результатов привели к установлению полуэмпирических формул.